ARTIFICIAL INTELLIGENCE IN CONTEMPORARY BUSINESS MANAGEMENT AND ITS IMPLICATIONS FOR DECISION-MAKING AND ORGANIZATIONAL PERFORMANCE - Hafni Juniyanti Hsb; Erizal Candra Efendi; Ruri Mustika; Wildan Hadi (Program Studi Manajemen Keuangan Syariah, 2026)
The development of Artificial Intelligence (AI) has brought significant changes in contemporary business management practices, particularly in the decision-making process and improvement of organizational performance. This article aims to conceptually examine the role of Artificial Intelligence (AI) in business management by emphasizing its implications for the quality of managerial decision-making and organizational performance. The research method used is a literature study by analyzing reputable national and international journals as well as academic books relevant to the topics of Artificial Intelligence (AI), decision-making, and organizational performance. Data analysis techniques are carried out through content analysis and thematic analysis to identify patterns, themes, and conceptual relationships between key concepts. The results of the study show that Artificial Intelligence (AI) plays a role as an enabler of data-based decision-making that is able to improve the accuracy, speed, and adaptability of managerial decisions. In addition, Artificial Intelligence (AI) contributes to improving organizational performance, both from operational and strategic aspects, when integrated in harmony with the organization's strategy and capabilities. The article also affirms that Artificial Intelligence (AI) can be understood as a strategic resource and dynamic capability that supports the creation of a sustainable competitive advantage. Theoretically, this study enriches the business management literature through the integration of AI with strategic decision-making and management theory, and provides practical implications for managers in designing effective Artificial Intelligence (AI) implementation strategies